Surgical Outcomes and Sociodemographic Disparities Across All Races: An ACS-NSQIP and NHIS Multi-Institutional Analysis of Over 7.5 Million Patients - Dany Y. Matar, BA; Samuel Knoedler; Anthony Y. Matar, BS; Sarah Friedrich, PhD; Harriet Kiwanuka, MD; Ryoko Hamaguchi, MD; Carla M. Hamwi, BS; Gabriel Hundeshagen, MD, MMS; Valentin Haug, MD; Ulrich Kneser, MD, PhD; Keisha Ray, PhD; Dennis P. Orgill, MD, PhD; et al. (Annals of Surgery Open)
Background:. This study aims to fill the gap in large-scale, registry-based assessments by examining postoperative outcomes across diverse races/ethnicities. The focus is on identifying disparities and comparing them with socioeconomic demographics. Methods:. In a registry-based cohort study using the 2008 to 2020 American College of Surgeons National Surgical Quality Improvement Program, we evaluated 24 postoperative outcomes through multivariable analysis, incorporating 28 preoperative risk factors. In a separate, independent analysis of the 2019 to 2020 National Health Interview Survey (NHIS) database, we examined sociodemographic racial/ethnic normative data. Results:. Among 7,504,734 American College of Surgeons National Surgical Improvement Database patients specifying race, 83.8% were White (WT), 11.8% Black or African American (B/AA), 3.3% Asian (AS), 0.7% American Indian or Alaska Native (AI/AN), 0.4% Native Hawaiian or Pacific Islander (NH/PI), 7.3% Hispanic. Reoperation trends reveal favorable outcomes for WT, AS, and NH/PI patients compared with B/AA and AI/AN patients. AI/AN patients exhibit higher rates of wound healing issues, while AS patients experience lower rates. AS and B/AA patients are more prone to transfusions, with B/AA patients showing elevated rates of pulmonary embolism, deep vein thrombosis, renal failure, and insufficiency. Disparities in discharge destinations exist. Hispanic patients fare better than non-WT Hispanic patients, contingent on race. Racial groups (excluding Hispanic patients) with superior surgical outcomes from the NSQIP analysis were found in the NHIS analysis to report higher wealth, better healthcare access, improved food security, greater functional and societal independence, and lower frailty. Conclusions:. Our study underscores racial disparities in surgical outcomes. Focused investigations into these complications could reveal underlying causes, informing healthcare policies to enhance surgical care universally.